Developing investment plan for low emission development interventions from rice production in Vietnam's Nationally Determined Contributions - The, Tran Van (2018)
Presentation by Tran Van The based on research conducted in collaboration with the government of Vietnam, IAE Vietnam, CCAFS, the Climate and Clean Air Coalition (CCAC), and USAID. International conference on agricultural emissions and food security: Connecting research to policy and practice 10-13 September 2018 Berlin, Germany